2022
DOI: 10.3390/ijms23169410
|View full text |Cite
|
Sign up to set email alerts
|

Uromodulin Regulates Murine Aquaporin−2 Activity via Thick Ascending Limb–Collecting Duct Cross−Talk during Water Deprivation

Abstract: Uromodulin, a urinary protein synthesized and secreted from the thick ascending limb (TAL) of the loop of Henle, is associated with hypertension through the activation of sodium reabsorption in the TAL. Uromodulin is a potential target for hypertension treatment via natriuresis. However, its biological function in epithelial cells of the distal nephron segment, particularly the collecting duct, remains unknown. Herein, we examined the regulation of uromodulin production during water deprivation in vivo as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Gene expression was analyzed by real-time RT-PCR as previously described [ 44 ]. Total RNA was extracted after a brief wash in phosphate-buffered saline from cells using a miRNeasy Mini Kit (QIAGEN, Tokyo, Japan) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression was analyzed by real-time RT-PCR as previously described [ 44 ]. Total RNA was extracted after a brief wash in phosphate-buffered saline from cells using a miRNeasy Mini Kit (QIAGEN, Tokyo, Japan) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty micrograms of protein were loaded for SDP-PAGE gel and transferred to nitrocellulose membranes. Western blotting was performed using established protocols [ 44 ]. Densitometry analysis was performed using ImageJ software 1.52a (National Institute of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Because vasopressin is a hormone secreted during dehydration or volume depletion, upregulated uromodulin secretion by vasopressin is considered a reasonable physiological response. Furthermore, urinary uromodulin secretion increases under dehydration condition and, conversely, activates AQP2 in collecting duct cells ( 43 ). These findings suggest that the TAL and collecting duct work cooperatively to retain sodium and water through cross-talk with uromodulin ( Fig.…”
Section: Functions Of Uromodulinmentioning
confidence: 99%
“…Uromodulin stimulates the expression of apical TRPV5 by inhibiting endocytosis ( 52 ). Uromodulin upregulates membrane proteins, such as TRPV5 and AQP2, by inhibiting endocytosis ( 43 , 52 ). Interestingly, the regulatory effect of uromodulin on apical membrane proteins is executed in a segment distant from its production, suggesting an autocrine-like function of uromodulin.…”
Section: Functions Of Uromodulinmentioning
confidence: 99%
“…In addition, it has been shown that UMOD enhances AQP2 phosphorylation and apical transport in mouse collecting duct cells treated with vasopressin analog dDAVP. The uromodulin-induced apicaltrafficking of AQP2 was attenuated via endocytosis inhibitor treatment, suggesting that uromodulin activates AQP2 through the suppression of endocytosis ( 87 ). Moreover, NKCC2 phosphorylation and activity are also regulated by the dDAVP-V2R-cAMP-PKA pathway, in which dDAVP promotes salt reabsorption by upregulating NKCC2 ( 88 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%